Post-COVID simultaneous onset of Graves' disease and ocular myasthenia gravis in a patient with a complex ocular motility impairment. Issue 3 (May 2023) - De Giglio, Laura; Sadun, Federico; Roberti, Cinzia; Polidori, Luigi; Gilardi, Marta; Altavista, Maria Concetta; Pennisi, Elena Maria
A 74-years-old man experienced severe diplopia one month after recovery from an uncomplicated SARS-CoV-2 infection. Neurological examination was normal whereas ophthalmological examination showed bilateral exophthalmos with a complex ocular motility disorder characterized bya pseudo-internuclear ophthalmoplegia after fatigue associated to impairment of elevation and infraduction. Antibodies against TSH and acetylcholine receptors were positive; subsequent hormonal tests, ultrasonography of thyroid gland, single fiber electromyography and orbit MRI confirmed the diagnosis of concomitant Graves Disease (GD) and Myasthenia Gravis (MG). The coexistence between MG and GD is not rare but simultaneous onset after viral infection is very unsual. The complex ocular disorder simulated a deficit of the oculomotor nerve nuclei, and on clinical examination it posed some problems in the diagnosis. We suggest that recent SARS-COV-2 infection may have triggered a complex autoimmune response.